2017
DOI: 10.1021/acsbiomaterials.7b00465
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Sulfobetaine-Stabilized Cu2O Nanoparticles and Their Biomedical Potential

Abstract: A novel approach using a zwitterionic sulfobetaine-based surfactant for the synthesis of spherical copper oxide nanoparticles (Cu2O NPs) has been applied. For the first time, N-hexadecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate has been used as stabilizer to control the size and morphology of Cu2O NPs. Several techniques, such as transmission electron microscopy (TEM), X-ray diffraction (XRD), and fluorescence spectroscopy, are used to investigate the size, structure, and optical properties of synthesized Cu2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Besides other mechanisms, mechanism of action of copper oxide NPs against microbes includes generation of oxidative stress and tendency of copper nanoparticles to alternate between cupric, Cu(II) and cuprous, Cu(I) oxidation states, making it unique from other metal nanoparticles 18 . Especially, Cu 2 O nanoparticles are widely abundant and have been reported to show lower toxicity, good environmental acceptability and remarkable broad-spectrum antibacterial and anti-superbug activity against a range of bacteria through generation of reactive oxygen species (ROS) and release of copper ions 22 25 . Zhou et al 25 reported remarkable antibacterial activity of Cu 2 O NPs on the superbugs “ methicillin-resistant staphylococcus aureus (MRSA)” and “ vancomycin-resistant enterococcus (VRE ) ” after being loaded on ZrP nanosheet matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides other mechanisms, mechanism of action of copper oxide NPs against microbes includes generation of oxidative stress and tendency of copper nanoparticles to alternate between cupric, Cu(II) and cuprous, Cu(I) oxidation states, making it unique from other metal nanoparticles 18 . Especially, Cu 2 O nanoparticles are widely abundant and have been reported to show lower toxicity, good environmental acceptability and remarkable broad-spectrum antibacterial and anti-superbug activity against a range of bacteria through generation of reactive oxygen species (ROS) and release of copper ions 22 25 . Zhou et al 25 reported remarkable antibacterial activity of Cu 2 O NPs on the superbugs “ methicillin-resistant staphylococcus aureus (MRSA)” and “ vancomycin-resistant enterococcus (VRE ) ” after being loaded on ZrP nanosheet matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major limitation of metallic copper oxide particles in the nano-size range is lack of sufficient stability of their dispersions due to their strong tendency to aggregate and form larger clusters to reduce the energy associated with their high surface area 22,25,27 . The cluster formation is followed by rapid sedimentation leading to loss of reactivity and bactericidal applications in which a nanometric size is required 27 .…”
mentioning
confidence: 99%
“…These results indicate successful formation of core–shell structure of Fe 3 O 4 @Cu 2 O nanocrystals. The X‐ray diffraction (XRD) characterization (Figure G) shows that concave spherical Fe 3 O 4 @Cu 2 O NCs match well with the standard of Fe 3 O 4 phase (JCPDS Cards: 26–1136) and Cu 2 O phase (JCPDS Cards: 34–1354) . The binding energies of Cu 2p, Fe 2p, and O 1s of resultant Fe 3 O 4 @Cu 2 O NCs were confirmed by X‐ray photoelectron spectroscopy.…”
Section: Resultsmentioning
confidence: 54%
“…The major limitation of nanoscale copper oxide particles is lack of su cient stability because of large energy associated with their high surface area of their dispersions and therefore they have strong tendency to aggregate and form larger clusters (Hotze et al 2010, Solioz 2018, Wozniak-Budych et al 2017, Zhou et al 2019. The cluster formation leads to rapid sedimentation which diminishes reactivity and activity of copper oxide, gained from nanomaterals size (Hotze et al 2010).…”
Section: Introductionmentioning
confidence: 99%